2022
DOI: 10.1002/ange.202202961
|View full text |Cite
|
Sign up to set email alerts
|

An Acid‐Regulated Self‐Blinking Fluorescent Probe for Resolving Whole‐Cell Lysosomes with Long‐Term Nanoscopy

Abstract: Long-term super-resolution imaging appears to be increasingly important for unraveling organelle dynamics at the nanoscale, but is challenging due to the need for highly photostable and environment-sensitive fluorescent probes. Here, we report a self-blinking fluorophore that achieved 12 nm spatial resolution and 20 ms time resolution under acidic lysosomal conditions. This fluorophore was successfully applied in superresolution imaging of lysosomal dynamics over 40 min. The pH dependence of the dye during bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…This strategy was first elucidated by Urano group by a landmark Sirhodamine derivative (HMSiR), 28,29 and later explored by different groups. [30][31][32][33][34][35] For the stabilizing strategy, hydrogen-bonding functional groups were directly introduced to the fluorophore scaffold, improving the stability of zwitterionic open-ring or leuco close-ring structure. [20][21][22] However, these strategies fail to tune the entire spectrum of the single-molecule blinking kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy was first elucidated by Urano group by a landmark Sirhodamine derivative (HMSiR), 28,29 and later explored by different groups. [30][31][32][33][34][35] For the stabilizing strategy, hydrogen-bonding functional groups were directly introduced to the fluorophore scaffold, improving the stability of zwitterionic open-ring or leuco close-ring structure. [20][21][22] However, these strategies fail to tune the entire spectrum of the single-molecule blinking kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid droplets (LDs) are unique organelles composed of core lipid elements surrounded by an amphipathic lipid layer containing several proteins. Importantly, the behavior and localization of LDs in cells are closely related to metabolic diseases like obesity, cancer, fatty liver, liver cirrhosis, hyperlipidemia, atherosclerosis, inflammation, and Alzheimer’s. Recent findings indicate that tumor progression is inextricably linked to LDs, with a higher content of LDs or LD-related proteins observed in cancer cells than in normal cells. , For example, a large number of LDs are found in renal cancers, specifically clear cell renal cell carcinoma, prostate cancer, pancreatic cancer, and colon cancer. Hence, the tracking and imaging of intracellular LDs are of significant importance for early cancer diagnosis. Several LD probes based on fluorophores, including Nile Red, BODIPY, AIEgens (Aggregation-Induced Emission luminogens), azafluorenone, benzothiadiazole, triphenylamine conjugate with bromobenzylidene (TPA-BI), and Stato-merocyanine, were recently developed. However, only monitoring the LDs in the live cancer cells is not a solution for cancer ablation . It requires an on-site spatiotemporally controlled delivery of anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Protein tags that react covalently with a small-molecule fluorophore provide more spectral options and better photostability but still require transfection of the cells under study and thus cannot be used in many nonmodel cell lines. Small-molecule fluorophores are well suited to address these problems, as they are compatible with virtually any cell type, and the labeling protocol requires only a simple same-day incubation. Indeed, commercially available LysoTracker dyes and recently reported LysoPB Yellow, among others, share these benefits. However, only a handful of lysosome probes, including LysoTracker Deep Red (LTDR), have been reported that absorb above 600 nm, which is required for long-term live-cell imaging, as higher-energy excitation is cytotoxic. Unfortunately, these dyes lack the photostability required for long-time-lapse SRM. …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, commercially available LysoTracker dyes and recently reported LysoPB Yellow, among others, share these benefits. 18 26 However, only a handful of lysosome probes, including LysoTracker Deep Red (LTDR), have been reported that absorb above 600 nm, which is required for long-term live-cell imaging, as higher-energy excitation is cytotoxic. Unfortunately, these dyes lack the photostability required for long-time-lapse SRM.…”
Section: Introductionmentioning
confidence: 99%